2021
DOI: 10.1007/s00122-021-03819-w
|View full text |Cite
|
Sign up to set email alerts
|

Wheat root systems as a breeding target for climate resilience

Abstract: In the coming decades, larger genetic gains in yield will be necessary to meet projected demand, and this must be achieved despite the destabilizing impacts of climate change on crop production. The root systems of crops capture the water and nutrients needed to support crop growth, and improved root systems tailored to the challenges of specific agricultural environments could improve climate resiliency. Each component of root initiation, growth and development is controlled genetically and responds to the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 189 publications
(228 reference statements)
1
62
0
Order By: Relevance
“…As described in Ober et al. (2021), the development of elite introgression lines for target root traits with similar above‐ground behavior would provide valuable materials for evaluating the value of the new trait in different environments or production. Likewise, the genetic framework described above and the availability of new genomics tools and advancements in the phenotyping methods would result in the plethora of genetic information related to RSA.…”
Section: Breeding Cereals For Improved Root Phenotypes Using Direct A...mentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Ober et al. (2021), the development of elite introgression lines for target root traits with similar above‐ground behavior would provide valuable materials for evaluating the value of the new trait in different environments or production. Likewise, the genetic framework described above and the availability of new genomics tools and advancements in the phenotyping methods would result in the plethora of genetic information related to RSA.…”
Section: Breeding Cereals For Improved Root Phenotypes Using Direct A...mentioning
confidence: 99%
“…For example, the introduction of rye chromosome into bread wheat resulted in the development of cultivars with 1B.1R translocation, and introduction of alien segment from Agropyron elongatum as 7DL.7EL translocation, which have good drought adaptability due to the deeper roots (Kaggwa et al, 2015;Placido et al, 2013). As described in Ober et al (2021), the development of elite introgression lines for target root traits with similar above-ground behavior would provide valuable materials for evaluating the value of the new trait in different environments or production. Likewise, the genetic framework described above and the availability of new genomics tools and advancements in the phenotyping methods would result in the plethora of genetic information related to RSA.…”
Section: Breeding Cereals For Improved Root Phenotypes Using Direct A...mentioning
confidence: 99%
“…Wheat root system is the main place for water and nutrient absorption. Its morphological and physiological characteristics have a close relationship with the growth and development of wheat aboveground part, especially caryopses, thus affecting the formation of wheat yield and quality ( Ober et al, 2021 ). The absorption of water by wheat roots is not only restricted by physical and mechanical properties of soil, but also affected by root growth and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…RSA plays a pivotal role in drought tolerance and nutrient acquisition and enhancing root systems is a target for improving climate resilience (recently reviewed by Ober et al 2021 ). Deeper roots can extract more water from subsoils, particularly during late developmental stages and grain fill, thereby improving yield in water limiting environments (Manschadi et al 2010 ).…”
Section: Progenitor Species Are a Source Of New Root System Architect...mentioning
confidence: 99%
“…tauschii (four QTLs) or tetraploid (durum; two QTLs) components of the synthetic. Ober et al ( 2021 ) reviewed the range of wheat trait variation reported in wheat as well as summarised available evidence linking deeper roots to access to soil moisture.…”
Section: Progenitor Species Are a Source Of New Root System Architect...mentioning
confidence: 99%